Answer:
2/3 x
![\sqrt[4]{y^2}](https://img.qammunity.org/2021/formulas/mathematics/high-school/l65t7aynn4e2bbmsfk0tts8y82e9p7fs2d.png)
Explanation:
( 16 x^11 y^8 / 81 x^7 y^6) ^ ( 1/4)
Simplify the expression inside the parentheses
Rewriting the constant
16/81 = 2^4 / 3^4 = (2/3) ^4
Next the x terms
x^11 / x^7
We know that a^b / a^x = a^ ( b-c)
x^ (11-7) = x^4
And finally the y term
y^8/ y^6 = y^( 8-6) = y^2
( (2/3) ^4 x^4 y^2) ^ ( 1/4)
We know that (ab) ^ c = a^ c * b^c
(2/3) ^4 ^ 1/4 ( x^4 ^ 1/4 ( y^2) ^ ( 1/4)
We know that a^ b^ c = a^ ( b*c)
(2/3) ^4 ^ 1/4 ( x^4 ^ 1/4 ( y^2) ^ ( 1/4)
( 2/3) ^ ( 4*1/4) * x^ ( 4*1/4) * y ^ ( 2 ^ 1/4)
2/3 * x * y ^ 2/4
2/3x y ^ 2/4
2/3 x
![\sqrt[4]{y^2}](https://img.qammunity.org/2021/formulas/mathematics/high-school/l65t7aynn4e2bbmsfk0tts8y82e9p7fs2d.png)